Fielding technique skills training model in under-17 athletes in cricket - Annisa Sulistianingsih; Achmad Sofyan Hanif; Taufik Rihatno (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The success of athletes in achieving success, one of which is the application of an appropriate training model, fun and easy to do, including in improving fielding technique skills. The purpose of this study was to produce a game-based fielding technique skill training model for cricket athletes U-17 years, with the result of a book product that can be used in cricket training. The research uses the research and development (R&D) method from Borg and Gall. The subjects of the study were the U-17 athletes at the PCI POPB Club DKI Jakarta and Central Java, totaling 48 people. The results of the study prove that from the evaluation results of test and measurement experts, game experts, and cricket experts, it is obtained that this product meets the criteria as a whole so that it can be used in the next stage of research. From the calculation results, for the mean difference test, the mean = 63.346, with t-count = 105,122 with df = 47 and p-value = 0.000 <0.05, which means there is a significant difference between the control group and the experimental group of the fielding technique skill training model. in the sport of game-based cricket for U-17 athletes. Thus, it can be concluded that the game-based fielding technique skill training model for U-17 athletes can effectively be developed and applied in training a series of fielding skill movement processes in cricket.